The metaphysics of meaning - Katz, Jerrold J. (Representation and mind., 1990)
In "The Metaphysics of Meaning, Jerrold J. Katz offers a radical reappraisal of the "linguistic turn" in twentieth century philosophy. He shows that the naturalism which emerged to become the dominant philosophical position was never adequately proven. Katz critiques the major arguments for contemporary naturalism and develops a new conception of the naturalistic fallacy. This conception, inspired by Moore, explains why attempts to naturalize disciplines like linguistics and logic, and perhaps ethics, will fail. He offers a Platonist view of such disciplines, justifying it as the best explanation of their autonomy, objectivity, and normativity. Katz examines in detail both Wittgenstein's arguments for a deflationary naturalism on which metaphysics transcends the limits of language, and Quine's arguments for a scientific naturalism on which epistemology is "an enterprise within natural science." He also analyzes related arguments, including Kripke's on rule following, Chomsky's for the psychological reality of language, Dummett's on the nature of theories Of meaning, and Davidson's and Putnam's against intensionalism. Katz shows that, although largely successful against the Fregean psychologized versions of intensionalism, all these arguments fail against an intensionalism that avoids both Fregeanism and psychologism. "The Metaphysics of Meaning concludes with a reassessment of the nature of philosophical problems. It explains their recalcitrance, without, like.